Continuous‐Variable Quantum Key Distribution with Gaussian Modulation—The Theory of Practical Implementations (Adv. Quantum Technol. 1/2018). Issue 1 (24th August 2018) - Laudenbach, Fabian; Pacher, Christoph; Fung, Chi‐Hang Fred; Poppe, Andreas; Peev, Momtchil; Schrenk, Bernhard; Hentschel, Michael; Walther, Philip; Hübel, Hannes
Abstract : Quantum key distribution allows two parties to establish an encryption key that, by the laws of physics, no other party can have knowledge on and therefore enables information‐theoretic communication security. In particular, quantum key distribution with continuous variables (CV‐QKD) represents a way to exercise quantum cryptography at a high technological readiness level taking advantage of the leading‐edge technological infrastructure provided by the telecom industry. The review by Fabian Laudenbach et al. (article number1800011 ) provides a detailed introduction to the mathematical tools and relations required for the security analysis of CV‐QKD and particularly deals with the effects of necessarily imperfect hardware components.